The Requirement For Guidance and Counseling In Secondary Schools Students: Exploring the Importance and Impact of Guidance and Counseling in Secondary Schools (Journal of Advances and Scholarly Researches in Allied Education, 2012)
With the introduction of thenew national policy on education in 1977, guidance and counseling became animportant issue in our schools system. Since then, guidance and counseling has beena regular topic in our dailies conferences and seminars.   For example,Nnadi (1984). Stressed its importance in our educational system and thepriority that should be given to it in out schools because of its usefulness intransition in the various stages of education.   Also, Nwabuisi (1984),emphasized on the necessity of proper guidance programme in schools if thecurrent national policy on education is to have the desired impact.